Crack and Cocaine Drug Dangers - Robbins, Paul R. (Paul Richard) (Springfield, NJ : Enslow Publishers, 1999)
Examines the social, medical, and legal aspects of crack and cocaine, the effects of their abuse, and different treatment programs.
Includes bibliographical references and index.
Keywords: Cocaine habit -- Juvenile literature. -- United States; Crack (Drug) -- Juvenile literature. -- United States; Crack (Drug); Cocaine; Drug abuse